Cannabis in Chinese Medicine: Are Some Traditional Indications Referenced in Ancient Literature Related to Cannabinoids? - Brand, E. Joseph; Zhao, Zhongzhen (Frontiers in Pharmacology, 2017)
Cannabis sativa L. (Cannabaceae) has a long history of utilization as a fiber and seed crop in China, and its achenes (“seeds”) as well as other plant parts have been recorded in Chinese medical texts for nearly 2000 years. While the primary applications of cannabis in Chinese medicine center around the use of the achenes, ancient indications for the female inflorescence and other plant parts include conditions such as pain and mental illness that are the subject of current research into cannabinoids such as cannabidiol (CBD) and ∆9-tetrahydrocannabinol (THC). However, little previous research has been conducted to analyze the Chinese medical literature in light of recent advances in the pharmacology and taxonomy of cannabis, and most of the relevant Chinese historical records have not yet been translated into Western languages to facilitate textual research. Furthermore, many key questions remain unresolved in the Chinese literature, including how various traditional drug names precisely correspond to different plant parts, as well as the implications of long-term selection for fiber-rich cultivars on the medical applications of cannabis in Chinese medicine. In this article, prominent historical applications of cannabis in Chinese medicine are chronologically reviewed, and indications found in ancient Chinese literature that may relate to cannabinoids such as CBD and ∆9-THC are investigated.